The effect of disability insurance receipt on labor supply - Eric French; Jae Song (Federal Reserve Bank of Chicago, 2009)
This paper estimates the effect of the Disability Insurance program on labor supply. We find that 30% of denied applicants and 15% of allowed applicants work several years after a disability determination decision. The earnings elasticity with respect to the after tax wage is 0.8. However, the labor supply of those over age 55, college graduates, and those with mental illness is not sensitive to allowance of benefits.
Keywords: 330; Erwerbsunfähigkeitsrente; Arbeitsangebot; USA